(3LQjeI GdCNP HGdKCQ h aTd GdYbhHGJ GdhVYjI ai GdbVGA YdjgG (B: s (3OQGSI ebGQfI ai GdJTQjY GdESdGei h GdbGfhf GdhVYi (B/ s - (3Rjf eQYi WfWGhi eMeOs; (3YHOGdYRjR QeVGf Sec (B: s ((3GdbGgQI (B: s (3Rjf eQYi WfWGhi eMeO (B: s, 2013)
(3jJfGhd GdHMK LQjeI GdCNP HGdKCQ h JhZdgG ai GdJGQjN GdEfSGfi efP hLhO GdEfSGf Ydi gPg GdCQV h GdeYQha Cfg EPG hLO GdeLfi Ydjg SdWI GdOhdI GdbGFeI JCNP Mbg ef GdLGfi jca ZGdHG Yf GdCNP HGdKCQ MjK bGeJ Hg GdMcheI GdbGFeI h gPG cGf GdCeQ ZjQ Pdc CNP KCQg HfaSg h gh GdMGOK GdBf ai Xd CMcGe GdbGfhf GdhVYi GdeUQi h ZjQg ef GdbhGfjf GdhVYjI GdeTGHgI(B. (3CXgQ GdHMK Cfg df jbVi bVGAG eHQeG Yd GdKCQ EdG HMce GdTQjYI GdESdGejI h gh JNjjQ GdeLfi Ydjg Hjf GdbUGU Ch GdOjI Ch GdYah(B. (3h gPG GdMce ajg JbOjQ dMQeI GdeLfi Ydjg h GdEYJHGQ HQCjI ai GdMce Ydi GdLGfi h gh eG jbVi Ydi LQGFe GdKCQ h jSGYO Ydi bHhd GdLGfi YVhG ai GdgjFI GdELJeGYjI EPG Je GdYah Yfg HeGd Ch HdG eGds
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdTQjYI GdESdGejIs
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdKCQ s; (3GdOjI s; (3GdbJd bUGUG s